Medicine donation programmes supporting the global drive to end the burden of neglected tropical diseases. (16th January 2021) - Bradley, Mark; Taylor, Rachel; Jacobson, Julie; Guex, Morgane; Hopkins, Adrian; Jensen, Julie; Leonard, Lynn; Waltz, Johannes; Kuykens, Luc; Sow, Papa Salif; Madeja, Ulrich-Dietmar; Hida, Takayuki; et al.
Abstract: Neglected tropical diseases (NTDs) are targeted for global control or elimination. Recognising that the populations most in need of medicines to target NTDs are those least able to support and sustain them financially, the pharmaceutical industry created mechanisms for donating medicines and expertise to affected countries through partnerships with the WHO, development agencies, non-governmental organisations and philanthropic donors. In the last 30 y, companies have established programmes to donate 17 different medicines to overcome the burden of NTDs. Billions of tablets, capsules, intravenous and oral solutions have been donated, along with the manufacturing, supply chains and research necessary to support these efforts. Industry engagement has stimulated other donors to support NTDs with funds and oversight so that the 'heath benefit' return on investment in these programmes is truly a 'best value in public health'. Many current donations are 'open-ended', promising support as long as necessary to achieve defined health targets. Extraordinary global health advances have been made in filariasis, onchocerciasis, trachoma, trypanosomiasis, leishmaniasis, schistosomiasis, intestinal parasites and others; and these advances are taking place in the context of strengthening health systems and meeting the global development goals espoused by the WHO. The pharmaceutical manufacturers, already strong collaborators in initiating or supporting these disease-targeted programmes, have committed to continuing their partnership roles in striving to meet the targets of the WHO's new NTD roadmap to 2030.